2021
DOI: 10.1002/hyp.14152
|View full text |Cite
|
Sign up to set email alerts
|

A two‐layer model for studying 2D dissolved pollutant runoff over impermeable surfaces

Abstract: Dissolved pollutants in stormwater are a main contributor to water pollution in urban environments. However, many existing transport models are semi-empirical and only consider one-dimensional flows, which limit their predictive capacity. Combining the shallow water and the advection-diffusion equations, a two-dimensional physically based model is developed for dissolved pollutant transport by adopting the concept of a 'control layer'. A series of laboratory experiments has been conducted to validate the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…After the rainfall on June 1, although there were two rainfall events, the pollutants attached to the roof were not discharged in time, due to the small rainfall amount and its short duration. The above experimental phenomena are like those of Zhang et al and Hou et al; Zhang et al established a transport model of dissolved pollutants based on two-dimensional physics and analyzed that the intensity and duration of rainfall events have significant effects on the transport rate of pollutants [31], while Huo et al systematically analyzed the relative effects of rainfall characteristics and environmental factors on soil nutrient loss using a structural equation model (SEM). The results showed that maximum rainfall intensity over a 30-min period and rainfall depth had a positive effect on soil nutrient loss [32].…”
Section: Runoff Rainwater Quality Controlmentioning
confidence: 95%
“…After the rainfall on June 1, although there were two rainfall events, the pollutants attached to the roof were not discharged in time, due to the small rainfall amount and its short duration. The above experimental phenomena are like those of Zhang et al and Hou et al; Zhang et al established a transport model of dissolved pollutants based on two-dimensional physics and analyzed that the intensity and duration of rainfall events have significant effects on the transport rate of pollutants [31], while Huo et al systematically analyzed the relative effects of rainfall characteristics and environmental factors on soil nutrient loss using a structural equation model (SEM). The results showed that maximum rainfall intensity over a 30-min period and rainfall depth had a positive effect on soil nutrient loss [32].…”
Section: Runoff Rainwater Quality Controlmentioning
confidence: 95%
“…The present study aims to isolate the specific effect of sediment trapping as represented by λ. As such, we neglect other effects not included in Equation (), such as flow infiltration into the bed (Akram et al, 2015), vertical and/or horizontal variability of flow and suspended sediments (Zhang et al, 2021), or effects of bedforms. We also neglect dispersion (ν$$ \nu $$ = 0), and we take h/q to be constant, consistent with the experimental conditions under study.…”
Section: Methodsmentioning
confidence: 99%